PCML composite aerogel with high adsorption performance and preparation method thereof
By combining PEI functionalized CNF/MXene with natural loofah to form PCML composite aerogel, the problem of insufficient adsorption performance of offshore crude oil leakage in the prior art was solved, efficient and environmentally friendly crude oil adsorption effect was achieved, and efficient adsorption capacity was maintained during multiple cycles.
Patent Information
- Application Number
- CN202510274327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has insufficient adsorption performance when dealing with offshore crude oil leakage, and traditional cleaning methods are prone to impurity in treatment or solvent residues, resulting in secondary pollution.
A PCML composite aerogel was designed to form a 3D porous aerogel with high adsorption performance by combining PEI-functionalized CNF/MXene with natural loofah. With the assistance of sunlight or photothermal, the aerogel can quickly heat up and improve the adsorption performance of crude oil.
It has achieved efficient adsorption of offshore crude oil and other pollutants, with excellent compression cycle regeneration performance and durability, avoided secondary pollution, and maintained efficient adsorption capacity during multiple cycles.
Smart Images

Figure CN119771284A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and in particular to a PCML composite aerogel with high adsorption performance and a preparation method thereof. Background Art
[0002] The importance of water quality is closely related to the quality of human life. Frequent offshore oil spills caused by industrial activities have attracted great attention from countries around the world. Most countries have established more complete emergency response mechanisms, improved their ability to respond to offshore oil spills and water protection, and thus protected the development of marine ecosystems, fisheries, tourism and other systems. Thermal energy can effectively reduce the ultra-high viscosity of crude oil and improve the adsorption performance of composite materials. The light energy generated by photons from sunlight or ultraviolet and infrared lasers is converted into kinetic energy, which is transferred to the adsorption material in the form of kinetic energy, causing the temperature to rise, thereby reducing the viscosity of crude oil. In recent years, there has been a lot of research on the application of solar thermal conversion performance to porous materials, and there has been an endless stream of research on the use of cellulose-based porous composite materials in biomass for selective adsorption. By adjusting the chemical composition and porous structure, the composite materials are suitable for different applications, for example, they can capture crude oil, light oil, heavy oil, organic solvents, heavy metal ions and harmful dyes. Physical adsorption is usually used to adsorb crude oil and organic solvents, using the pore structure and van der Waals force of the adsorption material to capture hydrocarbons in crude oil, and using the active chemical properties of the surface to capture organic solvent molecules. Dyes can be adsorbed by physical and chemical adsorption, of which chemical adsorption relies on the chemical bonding between the adsorbent and the dye. In view of the shortcomings of traditional cleaning agents, oil absorbent felts, oil booms, chemical cleaning agents and other methods to control and clean leaks in the adsorption process, in order to avoid secondary pollution of water bodies caused by unclean treatment or solvent residues, the development of green and environmentally friendly adsorption materials has gradually received attention. In the future, we can use environmentally friendly and degradable nanomaterials with the help of thermal energy to absorb crude oil or other pollutants in water bodies, gradually leading to an emerging cleaning technology trend.
[0003] The combination of nanocellulose and aerogel can be described as a 1+1 greater than 2 effect. It is widely used for its unique advantages such as loose pores, high porosity, low density, large specific surface area, environmental friendliness and low price. Lu Jiarui et al. used cellulose nanofiber CNF / polyvinyl alcohol (PVA) and methyltrimethoxysilane (MTMS) composite aerogel to absorb crude oil to a capacity of 51.7 g / cm2. -1 .
[0004] Luffa comes from natural loofah plants, most of which are natural plant cellulose. Its network structure of thick and thin fibers interweaving together forms a solid 3D porous biomass skeleton. Luffa can be compounded with activated carbon, polymers, etc. to further improve its adsorption performance. It often has more superior adsorption characteristics and is suitable for water treatment, air purification and other fields, and the adsorption effect is significantly higher than the sponge materials sold on the market. This superior structure helps to guide crude oil molecules into the internal micropores. Combining natural loofah with nanocellulose aerogel, using the porous structure and directional pipeline biomass skeleton of loofah, it shows good adsorption performance for a variety of pollutants (such as heavy metal ions, organic solvents, dyes, etc.). Wang Peilin and others designed Janus-structured MXene / CNF aerogel for solar evaporators, which has strong water transport and salt removal performance, all thanks to the loose and porous structural characteristics of the aerogel and loofah after combination. The evaporation rate under normal sunlight is only 30%, so if you want to achieve efficient adsorption of crude oil or enhance the adsorption of ions, you need to add photothermal conversion materials to the traditional sponge or aerogel. In recent years, a variety of photothermal materials have been introduced for photothermal-assisted adsorption, such as metal nanoparticles, semiconductors, carbon materials, etc. Among two-dimensional materials, Ti3C2 MXene, as a hot two-dimensional structural material, is known for its extraordinary conductivity, strong mechanical properties and high photothermal performance. In fact, the cleaning ability of MXene is also amazing. It is like an invisible guardian, quietly purifying polluted water sources, and adsorbing those stubborn ions and organic matter through the interaction of free groups. Ti3C2 MXene should have attracted much attention in the field of photothermal-assisted adsorption of crude oil and wastewater treatment, but its poor stability and easy oxidation of its own functional groups have severely limited its application in the development of photothermal aerogels. In order to enhance the adsorption function of composite materials, Polyethyleneimine (PEI) is frequently used in wastewater treatment, drug delivery and other fields. However, there is no report on the composite device that can adsorb crude oil and multiple impurities in wastewater while retaining high photothermal conversion performance. Nanocellulose with hydroxyl groups and MXene with rich groups such as hydroxyl and carboxyl groups can interact with PEI with amine groups to form excellent adsorption composite materials. Chen Zhicheng et al. prepared a porous aerogel composed of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane / MXene / carbon nanotubes / sodium alginate / sodium carboxymethyl cellulose for crude oil adsorption and separation performance of metals and dyes, but did not involve adsorption performance other than crude oil. Qi Mengyu et al. used a loofah skeleton and CNF / MXene as a simple filler to prepare a crude oil adsorption aerogel with high photothermal conversion temperature and photothermal-assisted. Yuan Zihui et al. modified cellulose fibers with PEI and then decorated them with metal organic frameworks (MOFs). They then prepared adsorption foams with polyurethane in situ foaming in three steps for the adsorption of anionic dye methyl orange, with an adsorption capacity of up to 936.5 mg g -1 . This study designed a 3D porous structure PEI / CNF / MXene / Luffa (PCML) multifunctional aerogel. CNF and MXene are used as functional fillers, which is conducive to more active sites being available for the adsorption of target substances. The CNF / MXene composite material functionalized with PEI has a more efficient and rapid crude oil adsorption capacity, and can quickly heat up under sunlight to assist in the capture of crude oil. Next, the composite aerogel is further cross-linked with glutaraldehyde and sodium dodecyl sulfate, which can be used to selectively absorb cationic and anionic dyes from a multi-mixed dye system.
[0005] Therefore, it is necessary to construct a PCML composite aerogel with multiple advantages such as strong adsorption capacity, simple preparation process, easy availability of raw materials, and good durability. Summary of the invention
[0006] In order to solve the problems mentioned in the above background technology, the present invention provides a PCML composite aerosol with high adsorption performance and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: A first aspect of the present invention provides a PCML composite aerogel with high adsorption performance, comprising a substrate prepared from natural loofah, and PEI-functionalized CNF / MXene loaded on the substrate.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned PCML composite aerogel, comprising the following steps: S1. Under acidic conditions, lithium fluoride and MAX phase-Ti3AlC2 are mixed and reacted to obtain MXene nanosheet dispersion; S2. adding CNF and MXene nanosheet dispersion into deionized water to obtain CNF / MXene suspension, adding PEI, glutaraldehyde and sodium dodecyl sulfate to obtain PEI-functionalized CNF / MXene suspension; S3. Soak the natural loofah in the CNF / MXene / PEI suspension, mix evenly, freeze-dry, and obtain a PCML composite aerogel with high adsorption performance, wherein P is polyethyleneimine, C is CNF, M is MXene, and L is natural loofah.
[0009] Preferably, the specific method of step S1 is as follows: first, lithium fluoride is added to a polytetrafluoroethylene container under stirring at 20-30°C, and hydrochloric acid is poured in for etching; secondly, MAX phase-Ti3AlC2 powder is slowly added to the above solution at 45°C, and reacted for 1-3 days. The obtained black suspension is repeatedly washed with ultrapure water until its pH value is 6.5-7.5, centrifuged, and the obtained precipitate is subjected to a water bath and ultrasonic treatment for 30 min to peel off the MXene nanosheets, and finally the obtained liquid is centrifuged at 2500-3500 r min -1 After centrifugation for 10 min, a uniform dispersion of MXene nanosheets was obtained.
[0010] Preferably, in S1, the mass ratio of lithium fluoride to MAX phase-Ti3AlC2 is 1:(1-2).
[0011] Preferably, in S1, the acidic condition is an aqueous solution of hydrochloric acid, nitric acid, or sulfuric acid.
[0012] Preferably, the specific method of step S2 is: first, CNF is added to deionized water, stirred evenly, and ultrasonicated for 20-40 minutes to form a CNF suspension, and then MXene nanodispersion is added to the above suspension, stirred for 4-8 hours to obtain a CNF / MXene suspension, and finally PEI is added, stirred for 2-4 hours, glutaraldehyde and sodium dodecyl sulfate are added, and stirred for 1-3 hours to obtain a PEI-functionalized CNF / MXene suspension.
[0013] Preferably, in step S2, the mass volume ratio of CNF, MXene nanosheets, PEI, glutaraldehyde and sodium dodecyl sulfate is (0.1-1g): (0.1-1g): (0.05-1g): (0.1-0.3ml): (0.05-0.2g).
[0014] Preferably, the specific method of step S3 is: first remove the gelatinous substance and wax layer on the surface of the natural loofah, immerse it in deionized water for washing, dry it at 50-70°C for 10-20h, cut the natural loofah into pieces, make no less than 2 circular through holes in each piece to maintain the inherent shape of the silk, place the natural loofah in a mold, add PEI functionalized CNF / MXene suspension, repeatedly press it in and absorb it, and freeze-dry it for 1-3 days to obtain PCML composite aerogel.
[0015] Preferably, the method for removing the colloid substance and wax layer on the surface of the natural loofah is: the natural loofah is washed and soaked in hot water at 70-90° C. for 1-3 hours, then ultrasonicated for 1-3 hours, and after cleaning with deionized water, it is soaked in an alkaline solution for 1-2 days.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The PCML composite aerogel prepared by the present invention has an ultra-light weight (63 mg cm -3 ), still has excellent compression cycle regeneration performance, CNF and MXene are used as aerogel fillers, MXene plays its efficient photothermal conversion performance, the two are connected to each other through the abundant active sites, forming PCM super hydrophilic aerogel, on the basis of PCM aerogel, by introducing the 3D structure of loofah skeleton, the mechanical properties of aerogel are improved by about 50 times.
[0017] 2. CNF and MXene, which are rich in hydroxyl groups on the surface, are usually easy to form covalent bonds or hydrogen bonds with other functional groups, which amplifies their utilization rate. CNF and MXene themselves can produce strong hydrogen bonds. It is worth noting that there may be multiple interactions, called hydrogen bonding interactions, which affect the mechanical properties of PCML aerogel. The hydroxyl groups contained in CNF and MXene can undergo grafting reactions with the primary and secondary amines of PEI. The addition of glutaraldehyde can not only induce cross-linking reactions with PEI, but also undergo Schiff base reactions with MXene. In addition, the addition of sodium dodecyl sulfate as a surfactant significantly promotes the internal ion exchange process of PCML aerogel, and sodium dodecyl sulfate itself also enters the aerogel as an intercalant. In summary, the various reaction mechanisms between groups are also one of the main reasons for changing the mechanical strength of aerogels in subsequent processes, which will further affect the adsorption properties of aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 In the figure, (a) the preparation process of PCML composite aerogel; (b) the etching process of Ti3C2 MXene nanosheets; (c) the ultralight PCML aerogel can stand on the flower; Figure 2(a) The time for complete crude oil adsorption and the optical images of PCML aerogels with different PEI contents at room temperature; (b) The optical images of PCML aerogels with different PEI contents after crude oil adsorption; (c) The adsorption capacity of PCML aerogels with different PEI contents; Figure 3 This is the crude oil adsorption diagram of photothermal-assisted PCML composite aerogel; Figure 4 is the water contact angle, adsorption of organic solvents and dyes of PCML composite aerogel; Figure 5 It is the compression performance and dye adsorption kinetics model diagram of PCML composite aerogel; Figure 6 are the tensile-strain graph and optical graph of the original loofah fiber; Figure 7 This is a diagram of the crude oil recovery process after the PCML composite aerogel absorbs crude oil and is pressed.
[0019] Figure 8 This is the adsorption capacity diagram of PCML composite aerogel after 5 cycles of regeneration. DETAILED DESCRIPTION
[0020] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.
[0021] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed in this document, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".
[0022] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.
[0023] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0024] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0025] Natural loofah was purchased from Taobao (China). CNF was a suspension of 2,2,6,6-tetramethylpiperidin-1-oxyl free radical oxidized cellulose nanofibers (1.35 wt%, pH = 7) produced by Tianjin Wood Elf Biotechnology Co., Ltd. MAX phase-Ti3AlC2 powder was purchased from Yiyi Technology Co., Ltd. (Jilin, China). Hydrochloric acid was from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China). Glutaraldehyde, sodium dodecyl sulfate, n-hexane, acetone, dichloromethane, chloroform, toluene, and ethyl acetate were purchased from Aladdin Chemical Co., Ltd. (Shanghai, China). Polyethylenimine (MW600, 99%), lithium fluoride, Congo red, methylene blue, methyl orange, and malachite green oxalic acid were purchased from MacLean Biochemical Co., Ltd. (Shanghai, China). Heavy crude oil was supplied by Zhongyuan Air Force (China). All materials and chemicals were used without additional purification. Deionized water was used in all experimental procedures of this work. Example 1
[0026] A method for preparing a PCML composite aerogel with high adsorption performance comprises the following steps: S1. First, 1 g of lithium fluoride was added to a polytetrafluoroethylene container under stirring at room temperature, and 30 mL of 9 M hydrochloric acid was poured in for etching. Then, 1.5 g of MAX phase-Ti3AlC2 powder was slowly added to the above solution at 45 °C and reacted for 2 days. The obtained black suspension was repeatedly washed with ultrapure water until its pH value was 7, centrifuged, and the obtained precipitate was treated with water bath and ultrasound for 30 min to peel off the MXene nanosheets. Finally, the obtained liquid was centrifuged at 2500-3500 r min -1 Centrifuge for 10 min to obtain a uniform dispersion of MXene nanosheets; S2. First, 0.12 g CNF was added to 3 mL deionized water, stirred evenly, and ultrasonicated for 30 min to form a CNF suspension. Then, 0.12 g MXene nanodispersion was added to the above suspension and stirred for 6 h to obtain a CNF / MXene suspension. Finally, 0.2 g 50% PEI aqueous solution was added and stirred for 3 h. 0.2 ml glutaraldehyde and 0.1 g sodium dodecyl sulfate were added and stirred for 2 h to obtain a PEI-functionalized CNF / MXene suspension. S3. First, the natural loofah was washed and soaked in 80°C hot water for 2 days, then ultrasonicated for 2 hours, and washed with deionized water. It was then soaked in an alkaline solution for 1.5 days to remove the gelatinous substance and wax layer on the surface of the natural loofah. It was then immersed in deionized water for washing and dried at 60°C for 15 hours. The natural loofah was cut into pieces, and three circular through holes were made in each piece to maintain the inherent shape of the silk. The natural loofah was placed in a mold, and the PEI-functionalized CNF / MXene suspension was added. It was repeatedly pressed in and absorbed, and freeze-dried for 1-3 days to obtain a PCML composite aerogel, in which P is polyethyleneimine, C is CNF, M is MXene, and L is natural loofah, denoted as PEI-0.2-CML. Example 2
[0027] The difference between this embodiment and embodiment 1 is that in step S2, 0.05 g PEI is finally added, which is recorded as PEI-0.05-CML, and the rest is exactly the same as embodiment 1. Example 3
[0028] The difference between this embodiment and embodiment 1 is that in step S2, 0.15 g PEI is finally added, recorded as PEI-0.15-CML, and the rest is exactly the same as embodiment 1. Example 4
[0029] The difference between this embodiment and embodiment 1 is that in step S2, 0.25 g of PEI is finally added, which is recorded as PEI-0.25-CML, and the rest is exactly the same as embodiment 1.
[0030] Comparative Example 1 The difference between this embodiment and embodiment 1 is that in step S2, 0 PEI is added last, and the rest is exactly the same as embodiment 1.
[0031] Comparative Example 2 The difference between this embodiment and embodiment 1 is that in step S2, 0 g of glutaraldehyde and 0 g of sodium dodecyl sulfate are added, and the rest is exactly the same as in embodiment 1.
[0032] Results and Discussion 1. Photothermal conversion assisted crude oil adsorption 0.1 g of the PCML composite aerogels prepared in Examples 1-4 and Comparative Examples 1 and 2 were placed in 30 mL of crude oil to simulate oil pollution cleaning, and simulated irradiation (1.0 kW m -² ) to promote the absorption of crude oil, and the weight of the aerogel before and after oil absorption was recorded. Afterwards, the saturated aerogel sample was compacted and dried. The absorption capacity (M) was calculated according to the following formula: M=(m2-m1) / m1
[0033] Among them, m1 and m2 represent the weight of PCML aerogel before and after absorbing crude oil, respectively. The results are shown in Table 1.
[0034] 2. Adsorption of organic solvents 0.1 g of PCML composite aerogel prepared in Examples 1-4 and Comparative Examples 1 and 2 was placed in 30 mL of dichloromethane until adsorption was saturated. The aerogel was taken out from the solvent and weighed. The adsorption capacity was calculated according to the mass of the aerogel before and after adsorption. The calculation formula was the same as that of crude oil adsorption. The results are shown in Table 1.
[0035]
[0036] like Figure 1 As shown, loofah is a common agricultural waste. Its microstructure is a natural network structure of coarse and fine combined with a coarse skeleton and fine branches, which greatly enhances the strength and stability of the composite material. Loofah has a large specific surface area and good porosity, which enables it to provide more active sites during the adsorption process, thereby improving the adsorption efficiency and being suitable for applications under various environmental conditions. PEI-functionalized CNF / MXene aerogel (PCM) itself has loose and porous structural characteristics, and the aerogel will not change after being placed for a long time, and has considerable stability. However, the mechanical properties of PCM aerogel are poor. On this basis, the loofah skeleton is introduced into it. The PCML composite aerogel prepared by PEI / CNF / MXene / Luffa has ultra-high photothermal conversion performance, and crude oil is quickly absorbed under the thermal assistance of simulated sunlight. Monolayer d- Ti3C2T prepared from Ti3AlC2(MAX) by acid etching x , the tightly packed blocky MAX transforms into the typical accordion-like m-Ti3C2T x The diameter of the composite aerogel was controlled between 4.5-4.7 cm, and the height was controlled between 1.4-1.8 cm. The obtained PCML aerogel could be placed on flowers without crushing the leaves and stamens of the flowers, which showed that the aerogel had a high molecular weight (63 mg cm -3 ) has the ultra-low weight characteristic. Even without the loofah skeleton, the aerogel formed by PEI-functionalized CNF / MXene is a loose porous structure with clearly visible pores, and the PCM aerogel can also be bent, pressure-resistant and pulled. However, the coarse and fine fibers inside the loofah structure are entangled, and the tensile-stress strain of the loofah is measured. The tensile curve of the loofah presents a multi-peak state, with the highest point being the main vein of the loofah, and the rest are extremely fine fibers inside. The addition of the loofah structure significantly increased the mechanical properties and crude oil adsorption of the subsequent PCML aerogel.
[0037] like Figure 2As shown, CNF has a loose and porous structure that can be filled into the loofah network, providing a complex internal channel network for the composite. At the same time, CNF also has high mechanical strength and good flexibility. MXene has excellent chemical and photothermal stability. First, this study prepared MAX by hydrochloric acid hydrolysis and ultrasonic exfoliation. Scanning electron microscope images show that the dense block MAX is converted into a typical potato chip-like m-Ti3C2T x . It can be seen that the multilayer MXene presents a block structure, while the prepared single-layer MXene has a multilayer structure with uniform pores. The results show that the PCML aerogel has cross-linked CNF and MXene. The viscous and fibrous gel material can be clearly seen in the gel functionalized with PEI. The state of the loofah skeleton wrapping the PEI / CNF / MXene aerogel can be observed, and the hollow structure of the loofah skeleton and the uniform distribution of thick and thin fiber filaments can be seen.
[0038] CNF and glutaraldehyde form a cross-linked network, and the hydroxyl groups of CNF and MXene form a second cross-link with sodium dodecyl sulfate to enhance the ion exchange performance for photothermal assisted adsorption. Compared with PCM, the prepared PCML aerogel has better compression performance.
[0039] like Figure 3As shown in the figure, in the natural environment, offshore crude oil spills frequently occur. In order to cope with this phenomenon, this study prepared composite aerogels for crude oil adsorption. First, four aerogels, CNF / MXene aerogels, CNF / MXene aerogels functionalized with different PEI contents, CNF / MXene / Luffa aerogels, and PEI-functionalized CNF / MXene / Luffa, were prepared to compare the crude oil adsorption rates at room temperature. Pure crude oil was added, and the speed of adsorption of about 3.0 g of crude oil in each group was comprehensively compared (the time consumed for complete adsorption). It can be seen that the adsorption performance of PEI-functionalized CNF / MXene aerogels is higher than that of CM and CML, and the presence of PEI significantly improves the adsorption performance of aerogels. With the increase of PEI content, the adsorption amount of PCML aerogel increases. However, the PEI content ratio of a certain group of samples is too high (more than 35%), which cannot fully react with CNF, but instead occupies the active sites on the surface of the composite aerogel, inhibiting further adsorption capacity. The treatment group with excessive PEI content will have a soft aerogel and cannot be weighed. The aerogel with 0.2g of 50% PEI had the best effect. Inspired by the adsorption performance of loofah and the excellent photothermal performance of MXene, PCML aerogel with the fastest adsorption speed was selected for photothermal-assisted crude oil adsorption. PEI-functionalized CNF / MXene / Luffa aerogel (PCML) was selected for subsequent adsorption experiments. With the assistance of sunlight, PCML aerogel can have super strong crude oil adsorption capacity. Studies have shown that crude oil viscosity can decrease rapidly with increasing temperature. By simulating sunlight with different irradiation intensities, the photothermal conversion performance of PCML aerogel and the photothermal-assisted crude oil adsorption effect were studied, and an infrared camera was used to record the real-time temperature changes. At 0.5 (0.5 kW m -2 ) sunlight, it took only 17 seconds to rise to 50 ° C, and it rose to 55.3 ° C in 90 seconds. Under 1 sun, the temperature of PCML aerogel rose rapidly to about 66 ° C in 8 seconds, rose to 81.4 ° C in 60 seconds, and finally stabilized at 84.8 ° C. Under 1.5 suns, it rose to 92.1 ° C in 60 seconds and stabilized at 95.9 ° C. Most importantly, under 2 suns, it rose to 103.6 ° C in 60 seconds and finally stabilized at a high temperature of 110.3 ° C, greatly reducing the viscosity of crude oil. Under sunlight (0.5-2.0kW m -2 ) There is no spontaneous combustion phenomenon under heating, which confirms its stability under in-situ heat generation conditions. Analysis shows that the high photothermal conversion performance of PCML aerogel comes from the rich and dense pore structure of PCML aerogel, the porous structure of cellulose as a secondary addition, the polyethyleneimine-assisted capture of light intensity and enhanced adsorption effect, and the Ti3C2T xThe plasma resonance (LSPR) effect of MXene and various factors assist the rapid heat generation of aerogels. According to various studies, the LSPR effect of MXene on the surface of aerogels has a wide range of absorption functions in the solar spectrum, which is consistent with the excellent photothermal performance of MXene shown in this study. The layered structure of PCML aerogel increases light adsorption and improves the photothermal conversion efficiency, which once again confirms that MXene is an excellent material with efficient and rapid heat generation. In addition, the adsorption performance of crude oil on the surface of PCML aerogel is analyzed by comparing the crude oil adsorption rate with and without sunlight irradiation. When a crude oil droplet (3.0 g) is dripped onto the upper surface of PCML aerogel without sunlight irradiation, it takes about 7.21 min after complete saturation penetration. However, when the same PCML aerogel is exposed to 1 sun (1.0 kW m -2 ), crude oil (5.0 g) can be completely absorbed by PCML aerogel within 1.23 min. As expected, the photothermal performance can significantly increase the crude oil adsorption rate of PCML aerogel, which is about 6 times faster than in the absence of light. PCML aerogel can absorb solar energy and generate heat energy, which increases the fluidity of crude oil on its surface and improves the adsorption rate. In this study, PCML aerogels were placed under different simulated sunlight irradiation, and crude oil adsorption during simulated sunlight irradiation was simulated. The changes in aerogel weight of each group of aerogels before and after the crude oil adsorption reached saturation were recorded (CM, CML, PCM, PCML). It can be found that the adsorption amount of aerogels without PEI (16.95 gg -1 ) is the lowest, while PCML aerogel (22.49 gg -1 ) is relatively the highest, and the saturated adsorption capacity of PCML aerogel under photothermal assistance can reach 29.61 gg -1 .
[0040] like Figure 4 As shown in the figure, the emission of organic solvents has caused serious pollution to the environment. Water pollution includes the wanton emission of various organic solvents. In order to remove organic solvents from water efficiently and harmlessly, most studies choose ultra-light aerogels for water pollution adsorption. In this study, PCML aerogel can adsorb a variety of light oils and heavy oils. The PCML aerogel was soaked in different organic solvents for 10 min, and its weight before and after was measured to determine its ability to adsorb organic solvents. The absorption capacity of PCML aerogel for different organic solvents is very different. Due to the large difference in the relative atomic weight of different solvents (crude oil can reach 960g mol -1 , while acetone has only 58.08 g mol -1), which also represents the great difference in viscosity between solvents. Among the adsorption of different organic solvents, this study selected chloroform (heavy oil) and n-hexane (light oil) as the concentrated 5 adsorption cycles for comparison. After the second repeated adsorption, the adsorption capacity of the aerogel will decrease significantly, but after five times, the adsorption capacity of PCML aerogel can still be maintained at 3.66 gg -1 and 7.03 gg -1 Overall, the PCML aerogel has a high absorption capacity for crude oil (20.61 gg -1 ) is much higher than other organic solvents, among which n-hexane, which has the lowest adsorption capacity, can reach 7.17 gg -1 This study only selected several representative common organic solvents (n-hexane, acetone, dichloromethane, chloroform, toluene, ethyl acetate). PCML aerogel, as an ideal material for adsorbing organic solvents, can play an important role in air purification, sewage treatment and other fields, helping to reduce the impact of organic solvents on the environment.
[0041] The adsorption capacity of an adsorbent is defined as the mass of the saturated adsorbate per gram of dry adsorbent, and it is one of the most important indicators for evaluating the adsorption performance of an adsorbent. Since CNF is an extremely hydrophilic material, and the hydrogen bonds between PEI and CNF / MXene maintain their original structure, the wet composite aerogel sample is very easy to collapse after contacting water molecules. This is because the PCML powder functionalized with PEI still has extremely strong hydrophilicity (water contact angle). On this basis, this study used PCML aerogel powder for adsorption tests. Taking CR dye as an example, this study conducted a single-factor test on the dye adsorption performance of PCML aerogel. The first is the adsorption capacity of 10 mg PCML aerogel in different concentrations of CR dye. The change in the adsorption amount of CR by PCML aerogel over time shows that the driving force of the concentration gradient leads to a higher adsorption amount at a higher CR dye concentration. As the dye concentration increases from 100 mg L -1 Increased to 600 mg L -1 The adsorption of PCML on CR increased from 244.30 mg g -1 Increased to 907.50 mg g -1 , the adsorption equilibrium can be reached in about 150 min. The above results show that PCML aerogel has a suitable pore structure and suitable charged functional groups, which are conducive to the interaction between active sites and dye molecules. On this basis, 20 μg mL -1 The dye solution was placed in CR solution with different pH values using HCl and NaOH. The adsorption capacity reached the highest value at pH 4, which was 2075 mg g -1 In an acidic environment with a pH of 3, the adsorption capacity can be as high as 2031.25 mg g-1 However, when the pH was 11, the adsorption capacity decreased to 1850.69 mg g -1 This also shows that PCML aerogel has excellent acid and alkali resistance, and it is easier to achieve efficient dye adsorption in an acidic environment. The adsorption capacity (M) of PCML aerogel for CR at different times showed a gradual increase, and it almost reached saturation at a certain time. Finally, the adsorption capacity of PCML aerogel (adsorbent) with different contents was measured. According to the above adsorption capacity determination formula, it was found that the adsorption capacity decreased significantly with the increase of aerogel content, but the adsorption rate was gradually increasing, but the overall adsorption rate remained above 85%. This also shows that the minimum aerogel powder can be used for the maximum adsorption in the process of dye adsorption, which provides the nearest reference plan for water pollution control and environmental protection. Subsequently, the adsorption performance of different types of cationic dyes and anionic dyes was comprehensively observed. First, after the PCML aerogel was ground into powder, a very small amount (10 mg) was added to the methylene blue, Congo red, methyl orange and malachite green dye solutions respectively. After 2 hours of continuous adsorption under stirring, among the four dyes, the aerogel has the most significant adsorption effect on the anionic dye Congo red. Within 40 minutes, only 10 mg of aerogel powder can adsorb 5 mg of dye to a transparent color. On this basis, 10 mg was added to adsorb the remaining three dyes, and it was found that malachite green could be completely adsorbed when 20 mg of aerogel powder was used. After adding 30 mg of PCML aerogel, methylene blue and methyl orange were also adsorbed. The above excellent dye adsorption performance shows that Schiff bonds and strong hydrogen bonds are formed between CNF, MXene, PEI, and GA through multiple complex cross-linking networks.
[0042] In summary, the PEI-functionalized CNF / MXene / Luffa3D structured porous dense aerogels prepared by a simple freeze-drying method in this study have an ultralight weight (63 mg cm -3 ), it still has excellent compression cycle regeneration performance. CNF and MXene are used as aerogel fillers. MXene plays its efficient photothermal conversion performance. The two are connected to each other through the abundant active sites to form PCM super hydrophilic aerogel. On the basis of PCM aerogel, the performance of the 3D structure aerogel is improved by about 50 times by introducing the loofah skeleton. In order to deeply study the excellent adsorption performance of PCML aerogel, this study discusses from three directions (crude oil, organic solvents, and ionic dyes). First, at room temperature, the adsorption capacity of PCML aerogel for crude oil is as high as 22.49gg -1After five consecutive adsorption and regeneration cycles, the crude oil adsorption capacity and removal efficiency of the PCML composite aerogel adsorbent did not decrease significantly, and the adsorption efficiency was still 95.91% at the fifth adsorption. -2 ) under 1 sun (1.0 kW m -2 ) assisted by PCML aerogel, 5.0 g crude oil can be completely adsorbed within 1.23 min, and the saturated crude oil adsorption capacity of PCML aerogel can reach up to 29.61 g -1 Secondly, this study selected six common organic solvents in water as pollution sources (toluene, ethyl acetate, dichloromethane, chloroform, acetone, and n-hexane), and used the weight of the aerogel before and after placement as an adsorption judgment indicator. Among them, the adsorption capacity of dichloromethane and chloroform was the highest, reaching 16.42 g / cm2, respectively. -1 and 16.29 gg -1 , the adsorption effect is extremely significant. Afterwards, after the aerogel is saturated with adsorption, the organic solvent and crude oil adsorption amount are compared. Even though the crude oil has a huge viscosity, the PCML aerogel shows extremely excellent adsorption performance. In the third part, the adsorption performance of four dyes, methylene blue, methyl orange, Congo red, and malachite green, on PCML aerogel is measured. Among them, the adsorption performance of CR is the most significant. Single factor test and adsorption kinetic mechanism study are carried out with Congo red as an example. It can be found that the adsorption time of PCML aerogel is 2.5h-3h, and the adsorption capacity is the largest when the pH is 4. In this process, the less aerogel content is used and the higher the concentration of adsorbed dye, the more adsorption capacity of PCML aerogel will be, but very little aerogel cannot achieve the expected purpose. In fact, the adsorption effect of 1-6mg aerogel is relatively excellent, which is also closely related to the sodium dodecyl sulfate added in the process of preparing aerogel as an important contributor to enhancing adsorption. The pseudo-secondary adsorption kinetics is used to explain the relevant mechanism of aerogel adsorption of CR. CNF / MXene / Luffa aerogel after PEI functionalization, in which strong hydrogen bonds are formed between CNF and MXene, and the amine groups in PEI also form multiple interactions with functional groups such as -OH. After that, the secondary cross-linking of glutaraldehyde further promoted the formation of aerogel. More and more crude oil adsorption equipment has begun to use solar energy. The development of adsorption treatment of offshore crude oil spills, organic solvents and water dyes is an important way to deal with environmental problems and water resource crises. By continuously strengthening technology research and development and application, it is possible to deeply adsorb offshore leaked crude oil, effectively improve the quality of the water environment, and thus protect the ecosystem and promote sustainable development.
[0043] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A PCML composite aerogel with high adsorption performance, characterized in that: It includes a substrate prepared from natural loofah, and PEI-functionalized CNF / MXene loaded on the substrate.
2. A method for preparing a PCML composite aerogel with high adsorption performance as claimed in claim 1, characterized in that: The steps include: S1. Under acidic conditions, lithium fluoride and MAX phase-Ti3AlC2 are mixed and reacted to obtain MXene nanosheet dispersion; S2. adding CNF and MXene nanosheet dispersion into deionized water to obtain CNF / MXene suspension, adding PEI, glutaraldehyde and sodium dodecyl sulfate to obtain PEI-functionalized CNF / MXene suspension; S3. Soak the natural loofah in the CNF / MXene / PEI suspension, mix evenly, freeze-dry, and obtain a PCML composite aerogel with high adsorption performance, wherein P is polyethyleneimine, C is CNF, M is MXene, and L is natural loofah.
3. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 2, characterized in that: The specific method of step S1 is as follows: first, lithium fluoride is added to a polytetrafluoroethylene container under stirring at 20-30°C, and hydrochloric acid is poured in for etching; secondly, MAX phase-Ti3AlC2 powder is slowly added to the above solution at 45°C, and reacted for 1-3 days. The obtained black suspension is repeatedly washed with ultrapure water until its pH value is 6.5-7.5, centrifuged, and the obtained precipitate is subjected to water bath and ultrasonic treatment for 30 min to peel off the MXene nanosheets, and finally the obtained liquid is centrifuged at 2500-3500 r min -1 After centrifugation for 10 min, a uniform dispersion of MXene nanosheets was obtained.
4. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 2, characterized in that: In the S1, the mass ratio of lithium fluoride to MAX phase-Ti3AlC2 is 1:(1-2).
5. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 2, characterized in that: In S1, the acidic condition is an aqueous solution of hydrochloric acid, nitric acid, or sulfuric acid.
6. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 2, characterized in that: The specific method of step S2 is: first, CNF is added to deionized water, stirred evenly, and ultrasonicated for 20-40 minutes to form a CNF suspension, and then MXene nanodispersion is added to the above suspension, stirred for 4-8 hours to obtain a CNF / MXene suspension, and finally PEI is added, stirred for 2-4 hours, glutaraldehyde and sodium dodecyl sulfate are added, and stirred for 1-3 hours to obtain a PEI-functionalized CNF / MXene suspension.
7. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 2, characterized in that: In the step S2, the mass volume ratio of CNF, MXene nanosheets, PEI, glutaraldehyde and sodium dodecyl sulfate is (0.1-1g): (0.1-1g): (0.05-1g): (0.1-0.3ml): (0.05-0.2g).
8. The method for preparing a PCML composite aerogel with high adsorption performance according to claim 1, characterized in that: The specific method of step S3 is: first remove the gelatinous substance and wax layer on the surface of the natural loofah, immerse it in deionized water for washing, dry it at 50-70°C for 10-20h, cut the natural loofah into pieces, make no less than 2 circular through holes in each piece to maintain the inherent shape of the loofah, place the natural loofah in a mold, add the PEI functionalized CNF / MXene suspension, repeatedly press it in and absorb it, and freeze-dry it for 1-3 days to obtain the PCML composite aerogel.
9. According to the method for preparing a PCML composite aerogel with high adsorption performance as described in claim 1, the method for removing the gelatinous substance and wax layer on the surface of the natural loofah is: the natural loofah is washed and soaked in hot water at 70-90°C for 1-3 hours, then ultrasonicated for 1-3 hours, and after washing with deionized water, it is soaked in an alkaline solution for 1-2 days.